DETERMINATION OF TOTAL PROTEIN CONTENT IN THE AERIAL PART OF PHLOMOIDES KIRGHISORUM USING THE KJELDAHL METHOD - Abdulhakimova, M.A.; Haydarova, D.R. (Research Focus International Scientific Journal, 2026)
In this study, the total protein content of the aerial parts of Phlomoides kirghisorum was determined using the Kjeldahl method. The plant material was collected during the vegetation period and dried under natural conditions. During the analysis, the total nitrogen content of the sample was determined, and the total protein content was calculated using a conversion factor of 6.38. The results showed that the nitrogen content of the plant material was 2.44%, while the total protein content was 15.57%. The obtained results indicate that Phlomoides kirghisorum is relatively rich in protein compounds. The determined protein content is an important indicator for evaluating the biological and pharmacological value of this plant species. The findings support the importance of comprehensive studies of medicinal plants and provide a scientific basis for their potential application in pharmaceutical and phytotherapeutic practices.